(untitled) (SCIENCE TIME JOURNAL, 2026)
Gastronomic terminology represents one of the most dynamic and culturally significant lexical layers in modern linguistics. The semantic structure of culinary vocabulary reflects national traditions, intercultural communication, social development, and historical transformations. This article investigates the semantic features of gastronomic terminology, including polysemy, metaphorization, borrowing, semantic shifts, and terminological adaptation. Particular attention is paid to the influence of globalization and multilingual interaction on the formation of gastronomic vocabulary. The research demonstrates that gastronomic terminology functions not only as a professional language system but also as a cultural and semantic phenomenon closely connected with human civilization and communication.